Sistem Informasi Status Surat Keterangan Penghentian Pembayaran (SKPP) - Yona Fransiska Dewi; Rizalul Akram (STMIK Budi Darma, 2019)
The progress of knowledge and technology in the present day is developing very rapidly, so that the information and data needs that are increasingly fast, precise and accurate are needed by the community. One example of a government agency that has made computer use one of its needs is the Langsa State Treasury Service Office in terms of data and information. In addition, the Langsa State Treasury Service office is a government agency that is close to the community and is a service office, especially employees who work with the government. This requires continuous changes along with the development of increasingly sophisticated science and technology. This research develops an information system that makes it easier for employees of the langsa treasury service office itself, and this research begins by collecting employee data, analyzing and designing systems.